2021
DOI: 10.1097/md.0000000000023677
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, double-blind, randomized, placebo-controlled phase III study evaluating efficacy and safety of octagam 10% in patients with dermatomyositis (“ProDERM Study”)

Abstract: Introduction: Dermatomyositis (DM) is an inflammatory myopathy characterized by distinct skin manifestations and muscle weakness. Intravenous immunoglobulin (IVIg) has been used off-label as adjuvant therapy in DM, but is not indicated for DM, due to lack of proven efficacy in a large randomized controlled trial. The objective of the ProDERM (Progress in DERMatomyositis) study was to evaluate the efficacy, safety and long-term tolerability of IVIg (Octagam 10%) in patients with DM in a randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 18 publications
0
27
0
3
Order By: Relevance
“…Clinical benefit corresponded to significant improvement in muscle cytoarchitecture, increased muscle fiber diameter, reduction of inflammation, revascularization, interception of complement deposition, and downregulation of inflammatory mediators at the protein, mRNA, and gene level [46,47,53,57]. A new large-scale randomized, placebo controlled, phase III study (ProDERM: Progress in DERMatomyositis) evaluating the efficacy and long-term tolerability of IVIg (Octagam 10%) up to 16 weeks with a 24-week extension phase has been now completed [115] and led, as of July 15, to FDA approval for this brand of IVIg for dermatomyositis [FDA orphan drug approval-Octapharma's Octagam 10% receives 7 years of market exclusivity for adult dermatomyositis. Octapharma AG.…”
Section: Inflammatory Myopathiesmentioning
confidence: 99%
“…Clinical benefit corresponded to significant improvement in muscle cytoarchitecture, increased muscle fiber diameter, reduction of inflammation, revascularization, interception of complement deposition, and downregulation of inflammatory mediators at the protein, mRNA, and gene level [46,47,53,57]. A new large-scale randomized, placebo controlled, phase III study (ProDERM: Progress in DERMatomyositis) evaluating the efficacy and long-term tolerability of IVIg (Octagam 10%) up to 16 weeks with a 24-week extension phase has been now completed [115] and led, as of July 15, to FDA approval for this brand of IVIg for dermatomyositis [FDA orphan drug approval-Octapharma's Octagam 10% receives 7 years of market exclusivity for adult dermatomyositis. Octapharma AG.…”
Section: Inflammatory Myopathiesmentioning
confidence: 99%
“…Von den zur Behandlung der Myositis eingesetzten Wirkstoffen ist für folgende eine Wirksamkeit auch gegen die Hauterscheinungen nachgewiesen worden: Glukokortikoide, Methotrexat [13], IVIG [14,15], Mycophenolatmofetil [16], Rituximab [17] und Stammzelltransplantation [18]. Azathioprin kann zwar eine Wirk-▶abb.…”
Section: Therapie Der Hautsymptomeunclassified
“…In some cases, the specific mechanisms of these autoimmune processes are still not elucidated [1]. IVIg has a featured role as an immunomodulatory and anti-inflammatory agent, mostly used "off-label", in autoimmune rheumatic diseases (ARD), except immunodeficiency and dermatomyositis [2,3]. In some small studies have shown the efficacy of IVIg in diverse ARD such as dermatomyositis/polymyositis (DM/PM), systemic lupus erythematosus (SLE) and antineutrophil cytoplasmic antibody-associated vasculitis (AAV) [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…IVIg has a featured role as an immunomodulatory and anti-inflammatory agent, mostly used "off-label", in autoimmune rheumatic diseases (ARD), except immunodeficiency and dermatomyositis [2,3]. In some small studies have shown the efficacy of IVIg in diverse ARD such as dermatomyositis/polymyositis (DM/PM), systemic lupus erythematosus (SLE) and antineutrophil cytoplasmic antibody-associated vasculitis (AAV) [2,[4][5][6]. IVIg is generally considered a safe therapy, and most of the side effects are mild and may be ameliorated with slower rates of infusion, premedication, and hydration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%